Evaluation of Occurrence and Population Variations of Culex quinquefasciatus Mosquitoes in Selected Areas of Jigawa State, Northwest Nigeria - A. Adeniyi , Kamoru; Adegbola Adesoye, Oluwaseun; A. Sadiq, Abubakar; Shuaibu , Tasiu; B. Mustapha, Muzammil; Lamidi , Yusuf; Adeogun , Adedapo; Akinsete , Israel; A. Ezeonuegbu , Blessing; C. Akinleye , Adewale; A. Oyeniran , Oluwatoyin (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Culex quinquefasciatus ecology and breeding sites, as well as the physical and chemical properties of their habitats are valid information to vector control. Thus, this study aimed to assess the occurrence and population size of Cx. quinquefasciatus mosquitoes that are captured in Jigawa State, northwest Nigeria. The dipping standard sampling method was employed for larval collection during the period from August to October 2023. Collected larvae were reared to adult stage and identified as Culex quinquefasciatus. Data obtained was analysed using SPSS version 20.0 and Analysis of Variance was employed to assess statistical difference. Culex mosquito were found in all breeding sites identified. The average number of identified males in Mai-lolo were 233.50±1.10 (12.40%) while that of female in the same location were 203.10±2.10 (7.76%). At Mai-alkama breeding sites the mean number of male mosquitoes were 264.22±2.00 (14.40%) which is significantly higher (ANOVA: P = 0.3220) than the values obtained in GRA (94.30±3.00) location. Notably, mean values of female Cx. quinquefasciatus Mosquitoes (281.00±0.00) in locations that includes Mai-rakumi is significantly higher (ANOVA: P = 0.2120) than the male (236.30±1.11) mosquitoes in the same location. Cx. quinquefasciatus is found to be abundant therefore, it is recommended that breeding habitats identified be eradicated and efforts to sustain public health campaigns on vector control management should be encouraged across the study location.